Implementasi Kebijakan Pengendalian Pencemaran Limbah Cair Hotel di Kota Yogyakarta Tahun 2017 - Oki Oktami Yuda; Eko Priyo Purnomo (Jurnal Administrasi Publik (Public Administration Journal), 2018)
The aims of this study are to determine the implementation of the policy of pollution control for hotel wastewater in Yogyakarta in 2017. This study applies a type of a qualitative research, data collection techniques through interviews with Yogyakarta City Environmental Service staff and documentation analysis. The results of the data analysis show that policy implementation is carried out through 3 activities, namely control, supervision and supervision, while the results of the implementation of the policy are implemented well as seen from the main targets of performance achievement in 2017 which reached 99.60%, efficient use of budget, adequate facilities and infrastructure, Clear Standard Operating Procedure  SOPs and encouragement from Non Governmental Organization (NGOs) that indirectly help in the implementation process, informative communication to hotel management, coordination with relevant stakeholders, Yogyakarta City Environment Agency acts as a mediator between the community and the hotel. Constraints that occur in the implementation of control policies are still lacking in human resources so that the implementation of supervisory activities becomes hampered.